50 за несчастное уравненьишко (х^2 - 3x^2)^2 - 2(х^2 - 3x^2) - 8=0

missiselllэльмир missiselllэльмир    2   11.07.2019 14:00    0

Ответы
deasd deasd  03.10.2020 01:17
В процессе заменяем y = x^2
(x^2-3x^2)^2 - 2(x^2-3x^2) - 8 = 0

4x^4 + 4x^2 - 8 = 0

4(y-1)(y+2) = 0

(y-1)(y+2) = 0

y = 1

y = x^2

x = 1 ; x = - 1 ; y = -2

x1 = 1 ; x2 = - 1
ПОКАЗАТЬ ОТВЕТЫ
sdmytryk8 sdmytryk8  03.10.2020 01:17
X^4-6x^4+9x^4-2x²+6x²-8=0
4x^4+4x²-8=0 |:4
x^4+x²-2=0
(x²)²+x²-2=0
x²=t ; t≥0
t²+t-2=0
D=1-4*1*(-2)=1+8=9
       -1+3
t1==2/2=1  
          2
      -1-3
t2==-4/2=-2 (не удовл. усл t≥0)
        2

x²=1
x=+-1
ответ:-1;1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра